EFFICIENCY UPGRADING IN UTILIZATION OF LIQUID-GLASS MIXTURES. PART 2. ELECTROPHYSICAL METHODS OF ACTION - A. N. Krutilin; Yu. Yu. Huminski; L. V. Kulbitskaya (Литьë и металлургия)
The methods of electrophysical influence on the structure of silicate binders and liquid-glass mixtures to improve their properties are generalized. Methods of influence such as ultrasonic, magnetic, electric and electrohydraulic are considered. Of great interest are The possibilities of combining physical and chemical methods of modification of liquid glass are lucrative ones. Application of electrophysical methods of influence allows to reduce quantity of expensive and scarce binding materials, to increase labor productivity at mixed preparation sites and at production of forms and cores shops. The electrophysical methods allow to reduce duration of preparation of silicate binding materials.